Meander-Line Technique for Size Reduction of VHF Patch Antenna in Lightning Energy Harvesting Applications - Yee Hui, Lee; Yi Lung, Then; Abadi, Chanik; Dayang Azra, Awang Mat (2025)
This paper presents a compact microstrip patch antenna design using a meander line structure for lightning energy harvesting applications. The antenna is designed to operate near 262.07 MHz, within the Very High Frequency (VHF) range where significant electromagnetic energy is emitted during lightning discharges. Based on studies of lightning signal characteristics, frequencies in the 30-300 MHz range are particularly rich in radiation from lightning phenomena such as stepped leaders and return strokes. To enable a practical energy-harvesting sensor, the proposed antenna is fabricated on an FR4 substrate (ϵr = 4.3, thickness = 0.16 cm) and optimized for size reduction. The meandered design achieves a compact footprint of 18 cm × 42 cm × 0.16 cm, resulting in a 54.6% reduction in size compared to a conventional rectangular patch antenna. Simulations were conducted using CST Microwave Studio Software, followed by prototype fabrication and measurement for performance validation.